Factors Influencing Investors’ Perception and Decision-Making in the Stock Market - Lamsal, Bishnu Prasad (Madhyabindu Journal, 2025)
This research employed a descriptive and analytical research design to investigate the perceptions of Nepalese investors towards the stock market, to analyze the relationship between different factors (investment decision, company-related variables, risk, and return-related variables, market-related variables) and investors' perceptions to examine the factors that impact in the investment decision. This research used primary data. The data was collected from 292 respondents who are residents of Nawalpur district. Inferential analysis was conducted in SPSS using statistical tools like correlation and regression to examine the relationships between dependent and independent variables, as well as to assess how various factors influence investors' perceptions. The study revealed that investment decisions, company-related variables, risk, and return-related variables, and market-related variables are mostly considerable factors before investing in the stock market.